Turkey Red Oil as a Renewable Leveling and Dispersant Option for Polyester Dyeing with Dispersed Dyes - Jully Schmidt Pinto Filippi; Angelo Oliveira Silva; Cintia Marangoni; Jeferson Correia; José Alexandre Borges Valle; Rita de Cassia Siqueira Curto Valle (Textiles, 2023)
The objective of this work was to evaluate Turkey red oil as a renewable dispersant and leveling option for dyeing polyester knitted fabric with disperse dyes. The dyeing results were evaluated by measuring the color at several positions of the dyed samples to verify the levelness. In addition, the amount of residual dye was evaluated. Migration tests were also carried out to evaluate the leveling effectiveness of Turkey red oil. Wet rubbing and washing fastness analysis, hydrophilicity, thermogravimetric analysis (TGA), surface analysis with scanning electron microscopy (SEM) and modification of functional groups by FTIR were also carried out. The results obtained in the analyses show that Turkey red oil is efficient as a dispersant and leveling agent when compared to the well-known sodium naphthalene sulfonate. It is concluded that Turkey red oil reduces the time of the dyeing process and consequently its energy consumption, and reduces the amount of effluent generated while improving hydrophilicity and fastness, thus being a renewable and sustainable option for current products based on petroleum.